1988
DOI: 10.1159/000199768
|View full text |Cite
|
Sign up to set email alerts
|

Interdigestive Gastroduodenal Motor Activity in Subjects with Increased Gastric Acid Secretion

Abstract: The interdigestive gastroduodenal motor activity was studied in 7 patients with active duodenal ulcer and increased gastric acid secretion, in 7 patients with hypersecretory gastroduodenitis and in 7 subjects with normal acid secretion, in whom the increase in acid secretion was obtained by means of the intravenous administration of an H2 agonist, Impromidine. The gastroduodenal motor activity was recorded manometrically for about 200–300 min in basal conditions to obtain at least two subsequent act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…Gastroduodenal motility was recorded by means of a 6-lumen manometric probe with lateral holes 5 cm part indicated by radiopaque markers following a method described in detail elsewhere [4], The cath eters were perfused with an Artidorfer pump (Arndorfer Medical Specialties, Greendale, Wise., USA) and connected to Statham P-23 Db external pressure transducers (Statham Laboratories Inc., Puerto Rico) and to a Beckman R 612 polygraph (Beckman Instru ments, Schiller Park, III.). After an overnight fasting of 14 h the manometric probe was positioned under radiologic control with one recording hole in the gas tric corpus, two in the gastric antrum, and three in the proximal duodenum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroduodenal motility was recorded by means of a 6-lumen manometric probe with lateral holes 5 cm part indicated by radiopaque markers following a method described in detail elsewhere [4], The cath eters were perfused with an Artidorfer pump (Arndorfer Medical Specialties, Greendale, Wise., USA) and connected to Statham P-23 Db external pressure transducers (Statham Laboratories Inc., Puerto Rico) and to a Beckman R 612 polygraph (Beckman Instru ments, Schiller Park, III.). After an overnight fasting of 14 h the manometric probe was positioned under radiologic control with one recording hole in the gas tric corpus, two in the gastric antrum, and three in the proximal duodenum.…”
Section: Methodsmentioning
confidence: 99%
“…In normal subjects the interdigestive gas troduodenal motility is inhibited by acid, either it is infused intraluminally [1,2], or increased by sham feeding [3], We have ob served that in hypersecretory duodenal ulcer the cyclic gastroduodenal motility shows a lower-than-normal frequency and duration of activity fronts of the migrating motor complex (MMC) [4], This motor pattern is similar to that observed in other hypersecre tory states either spontaneous and induced by secretagogues [4], Although controversy exists about a direct relationship between ulcer activity and acid secretion [5][6][7], the existence of a consistent proportion of duo denal ulcer patients, who share an increase in acid secretion during ulcer reactivation and a decrease during remission, cannot be denied. Consequently, the increase in acid secretion that would take place during ulcer activity in these patients should inhibit gas troduodenal motility, whereas the normal ization of acid secretion during the remis sion of the ulcer disease should be associated to a normalization of the cyclic motility.…”
Section: Introductionmentioning
confidence: 99%
“…In the fasted state, acid suppression increases phase 3 migrating motor complex (MMC) activity (‘housekeeping contractions’ that clear the bowel of undigested debris), whereas stimulating gastric acid secretion decreases MMC activity [10, 11]. This is likely due to alkaline pH in the duodenum triggering this contraction pattern [10].…”
Section: Gastric Acid and Motilitymentioning
confidence: 99%
“…Studies have shown that intravenous infusion of gastrin increases antral activity and delays gastric emptying [16]. Moreover reduced gastric secretion volume on H 2 RAs or PPIs would also be expected to slow gastric emptying [11]. However, the relative importance of acid suppression on secretion volume and motility with regard to gastric emptying is unknown.…”
Section: Gastric Acid and Motilitymentioning
confidence: 99%
“…Meals induce irregular contractions for a considerable period of time postprandially, and the quiescent phase (phase I) begins after the meal activity has subsided. Age-related changes have been documented, but not until the eighth or ninth decade of life (4). Patterns of small bowel motility in older adults have been documented via ambulatory manometry monitoring by Husebye and Engedahl (11).…”
Section: Gastric and Small Bowel Motilitymentioning
confidence: 99%